Comparison of Term Recognition and Awareness in Blended Classes of JavaScript and PHP Programming (Asian Education Studies, 2017)
A lecture course is provided by projecting slides on contents of the lecture course on a screen and the grammar in textbook and JavaScript program examples are explained in a lecture course on programming. It was then followed by explanation with materials describing program examples to practice the grammar and exercise problems. We conducted exercises to prepare programs in exercise problems with reference to the program examples. Instructions were given to complete the program during the lecture course as soon as possible, and the students were asked to submit the program and report files using the functions of e-learning. During the 14th week, each student was asked to prepare a program of voluntary subject he or she came up with, execute it and evaluate one another. With reference to the results, they were asked to correct them by the final 15th week and to evaluate one another again in the 15th week. The degree of term recognition and awareness were investigated before and after the lecture course. This article reports on the results obtained regarding this information on JavaScript programming. Then the difference between JavaScript and PHP programming is reported by comparing them with the results regarding PHP programming reported previously.